81 A study on the knowledge and awareness of cervical cancer among college students and assessing the impact of training sessions on cervical cancer awareness. (13th November 2020) - Rajanbabu, A; Patel, V
Abstract : Background: Cervical cancer is a major public health problem in India. In India there is a need for an intensive and sustained effort from health workers to improve awareness in order to increase prevention and screening. This study is an attempt to assess the knowledge of college students from various institutions about cervical cancer and to evaluate the impact of a cervical cancer awareness program on their knowledge. Material and Methods: Multiple training sessions on cervical cancer awareness was conducted in January and February 2020 at various colleges around Kochi, Kerala, India. A pre and post awareness session questionnaires were administered which included fifteen questions covering various aspects of cervical cancer screening and prevention. Results: The study was conducted in five different colleges across the district. Total of 485 students attended the awareness sessions and 449 were willing to participate in the study. Out of these students 160 were Para medical students and 289 non medical students. Knowledge about cervical cancer, methods of screening and prevention, benefits of vaccination were all low before which significantly improved post awareness session. The paramedical students performed significantly well than non medical students in the pre test but the post test scores showed the knowledge levels were similar in both the groups with the non medical students even outperforming paramedical students in certain areas. Conclusions: The awareness sessions improved the knowledge about cervical cancer and methods for prevention in both medical and non medical students. After the awareness session, majority of the students felt more knowledgeable and safe.